Analisis Persediaan Bahan Baku Cireng Pada Perusahaan XYZ Dengan Metode EOQ Menggunakan Software POM-QM - Sugeng Setyabudi; Rizqi Novita Sari (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Inventory or stock is stored material or goods that will be used to fulfil a specific purpose. An inventory management system is a set of control policies to determine the level of inventory that must be maintained. XYZ Company is a food company that produces Cireng. In the production process, the amount of demand received by the company varies from period to period. Based on the existing data, there is too much raw material stock that causes high storage costs for the company. Therefore, the EOQ method is needed to manage the company's inventory. From the data processing carried out in the POM-QM software, the output is obtained for tapioca flour raw materials where the total cost is Rp. 404,034,000 and the reorder point is 8 units, the output of the garlic raw material data where the total cost is Rp. 397,513,200 and the reorder point is 5 units, while the output of the flavouring raw material data where the total cost is Rp. 392,749,500 and the reorder point is 6 units. So as to obtain the optimal amount of inventory in each order, the total cost incurred and the reorder point value for each raw material of the XYZ company.